THE MEANING OF FINANCIAL LITERACY AND DIGITAL MARKETING FOR MSMES - Candra Puspita Ningtyas; Maulidia Berlianti; Muh. Husriadi (CV. Adiba Aisha Amira, 2026)
Digital transformation has transformed the management and marketing patterns of micro, small, and medium enterprises (MSMEs), yet many MSMEs still face limitations in financial literacy and optimal use of digital marketing. This condition is important to examine because both capabilities influence the efficiency, competitiveness, and sustainability of businesses in Kendari City. This study aims to describe the meaning of financial literacy, digital marketing, and their integration in the business practices of MSMEs in Kendari City. The study used a qualitative phenomenological approach with data collection techniques through in-depth interviews, observation, and documentation of purposively selected informants. Data analysis was conducted using the Miles and Huberman model through data reduction, data presentation, and drawing conclusions. The results show that financial literacy is defined as the ability to manage cash flow, separate personal and business finances, and utilize profits productively. Digital marketing is understood as a means of promotion and market expansion through digital media. The integration of the two strengthens business efficiency, increases competitiveness, and supports the sustainability of MSMEs. The implications of this study emphasize the importance of integrated training between financial literacy and digital marketing for strengthening local MSMEs.